Strategies of handling difficult situations by young people on the example of the research among young judo athletes - Janowska, Patrycja; Pujszo, Małgorzata; Stępniak, Robert (Journal of Education, Health and Sport, 2019)
There were 38 young judo athletes, aged from 9 to 17 years old, who took part in the research during their summer camp. There were 24 boys and 14 girls who completed the questionnaire ‘My strategies of handling difficult situations’ published in ‘Niezbędnik Dobrego Nauczyciela’ edited by prof. dr hab. Anna Izabela Brzezińska in the series IV ‘Monitoring the development during childhood and adolescence TOM 5 supplement’ by Anna I. Brzezińska, Julita Wojciechowska, Beata Ziółkowska, Aleksandra Kram and Marta Molińska with the subtitle ‘Tool box- Early stage of adolescence – How to collect information about teenagers and his environment?’ designed for teens aged: 11/12–14/15 years old. The questionnaire ‘My strategies of handling difficult situations’ consist of 12 statements which are grouped into three subgroups for 4 items in each describing three strategies of handling situations: ‘I’, ‘No one’ and ‘Others/ Adults’. Items in strategy ‘I’ describes teenagers who while in difficult situation try to rely on themselves, have high sense of influencing actions and life situations. People with ‘I’ strategy focus on solving the problem themselves; however, having problems with asking for help. Items describing ‘No one’ strategy are characterized by a passive attitude towards difficult situations. People with that approach to difficult situations avoid confrontation and do not put the blame on themselves. Items presenting ‘Others/Adults’ strategy describe teenagers who in difficult situations turn to adults for instructions on how to cope with them. They tend to blame others for their failures. Frequently they think that it is impossible to avoid difficult situations and their abilities are not good enough to handle them. Accepted definitions allowed for analysis of strategies used by teenagers to handle difficult situations on the example of young judo athletes.Gathered data was statistically processed using Excel 2006 and Statistica 7.0.Strategies